P45 OUTCOME AFTER ACUTE TYPE A AORTIC DISSECTION: THE ROLE OF AN AORTIC TEAM AND AN AORTIC REGIONAL NETWORK. (18th May 2022) - Lechiancole, A; Vendramin, I; Piani, D; Sponga, S; De Manna, D; Calandruccio, R; Brindicci, I; Bressan, M; Livi, U
Abstract: Background: The outcome of acute type–A aortic dissection (A–AAD) repair is strictly related both to surgical factors and patient conditions. Improvement in surgical experience and in diagnosis and treatment protocols could significantly increase survival for patients affected by A–AAD. The aim of this study was to assess the impact on patients outcomes of a standardized integrated surgical approach and of a regional aortic hub and spokes network. Materials and Methods: From 2004 to 2021, a total of 258 patients underwent repair of A–AAD. In 2010 in our Institution was created the Aortic Team, with cardiac surgeons dedicated on the treatment of aortic pathologies, while in 2017 was created a regional aortic network between hub and spokes in order to standardize the diagnosis and treatment algorithm. Thus, patients were distributed among three periods: 2004–2010 (Era 1, n = 90), 2011–2016 (Era 2, n = 87), and 2017–2021 (Era 3, n = 81). Results: Baseline demographic characteristics of the groups were similar. Compared to Era1 and Era2, clinical status at time of operation was better in Era3, because of less rates of malperfusion (16% vs 11% vs 4%, p = 0.01) and hemodynamic compromise (34% vs 38% vs 22%, p = 0.07). Patients of Era 3 were less likely to Axillary artery cannulation was almost routinely used in Eras 2 (86%) and 3 (91%) while femoral artery was mainly cannulated in Era 1 (91%) (p < 0.01). Retrograde cerebral perfusion was predominantly used in Era 1 (60%) while antegrade cerebral perfusion was preferred in Eras 2 (94%, ) and 3 (100%); (p < 0.01). There was a significant increase of arch replacement procedures from Era 1 (11%) to Eras 2 (33%) and 3 (48%) (p < 0.01). Frozen elephant trunk was mainly performed in Era 3. Operative mortality was 13% in Era 1, 11% in Era 2, and 4% in Era 3 (p = 0.07, p = 0.03 between Era 1 and Era3). Actuarial survival at 3 years is 74%, in Era 1, 78% in Era 2, and 89% in Era 3 (p = 0.05). Patients of Era 3 received less re–exploration for bleeding (p = 0.02) and less high inotropic support (p = 0.04). Conclusions: With increasing experience and a more aggressive approach, including total arch replacement, repair of A–AAD can be more tailored to patients conditions, being performed with low operative mortality in many patients. Moreover, patient care and treatment by a multidisciplinary regional organization allows faster diagnosis and effective clinical stabilization allowing to further improve early and late outcomes.